FAKTOR- FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA RS. PANTI WALUYO SURAKARTA - Enggi Silvia Tiarawati,; Ismunawan, (Jurnal Cakrawala Ilmiah, 2023)
This study aims to determine and analyze the influence of information technology sophistication, user participation, user capabilities, formalization of system development individually or simultaneously on the performance of accounting information systems. This research was conducted at RS. Waluyo Orphanage Surakarta. This type of research is quantitative research, using primary data sources through distributing questionnaires to 15 employee divisions in the accounting information system performance section with a total of 60 respondents with data analysis tools, namely multiple linear regression and classical assumption tests. The results showed that the sophistication of information technology and the ability of users had a significant effect on the performance of accounting information systems, while user participation and the formalization of system development had no significant effect on the performance of accounting information systems.